Garrett eaudiobook - Bennett, Sawyer (Cold Fury Hockey, 2015)
Carolina Cold Fury star Garrett Samuelson never wants to miss out on a single minute of fun. Whether he's playing hockey, hanging out with friends, or walking the red carpet with a new date on his arm, he lives every day to the fullest. When he meets Olivia Case, he sees someone who's exactly his type—confident, sexy, and smart. But the more he pursues her, the more Garrett shares a side of himself that other women don't normally get to see. Olivia has been keeping a secret. She's undergoing treatment for some serious medical issues, and she doesn't have time for a relationship with no guarantees—especially one with a hot-as-sin womanizer who won't take no for an answer. But as she gets to know the real Garrett, Olivia can't help falling for him . . . hard. To reveal the truth would mean risking everything—but you can't score without taking the tough shots.